Mapping Mental Well-being in Cities: A Narrative Review of Urban Mental Health Determinants - Aryuni, Muthia; Holis, Ade; Marwah, Sopa Siti (Sinergi International Journal of Psychology, 2023)
Urbanization has significantly reshaped social and environmental landscapes, posing complex challenges to mental health in densely populated areas. This narrative review aims to explore how urban stressors—both social and physical—influence psychological well-being, and what interventions may mitigate their impact. Literature was collected through comprehensive searches in PubMed, Scopus, and Google Scholar using keywords such as "urban mental health," "social determinants," and "environmental factors." Inclusion criteria focused on peer-reviewed studies examining urban populations and mental health correlations. Results consistently highlight the protective role of strong social networks in reducing symptoms of anxiety and depression, while isolation is a major risk factor. Environmental stressors such as poor housing, pollution, and lack of green spaces exacerbate psychological distress, particularly among marginalized populations. Access to mental health services remains unequal, with systemic barriers like funding gaps and service fragmentation limiting outreach. Discussion reveals that while findings align with classical theories, new data support the integration of technological, environmental, and community-based approaches. Policy recommendations include promoting green urban design, investing in community programs, and expanding access to digital mental health tools. In conclusion, enhancing social support and equitable access to services are vital strategies for improving mental health outcomes in urban settings.